Application of Quizizz Media in Learning to Analyze the Building Elements of Poetry for Class X Students of MAN 2 Gorontalo Regency - Trywidarti S Magu; Asna Ntelu; Herson Kadir (Raja Zulkarnain Education Foundation, 2026)
The purpose of this study is to utilize Quiziz media to help students better remember the material. With results that can be read or downloaded directly and displayed on an LCD screen, Quiziz also functions as a daily assessment tool, motivating students to be enthusiastic and achieve the best grades. This research was conducted at MAN 2, Gorontalo Regency, in 2024. The number of students or population at the time of the study was 8 people. The descriptive method is a research method used to describe or explain an existing phenomenon or situation, without attempting to change or manipulate the existing variables. In this study, the descriptive method was used to describe or explain the application of Quizizz media in learning to analyze the building blocks of poetry. Quantitative data were obtained through pretests and posttests, which were analyzed using descriptive statistical means and to observe differences in learning outcomes before and after the application of Quiziz. Meanwhile, qualitative data were collected through learning observations and documentation to explore in-depth the planning, implementation, and evaluation processes, obstacles, and solutions applied during the use of Quiziz media. The results showed that the application of Quizizz media can improve student learning outcomes in analyzing the building blocks of poetry. Factors influencing student learning outcomes include technical factors, teacher readiness, student readiness, the environment and facilities, and psychological and social factors. Solutions to address these inhibiting factors include providing alternative learning modes, improving teacher and student readiness, optimizing the environment and facilities, and employing psychological and social approaches. The results of this study indicate that Quizizz media can be used as an innovative method to improve the quality of learning and student learning outcomes.